Friction and Wear in Timing Belt Drives - B. Stojanovic (Tribology in Industry, 2010)
Timing belt tooth goes into contact with a drive pulley, stretched to the maximum, because of the previous tension. When the contact begins the peak of the belt tooth makes the contact with the outer surface of the pulley teeth. The process of the teeth entering into the contact zone is accompanied with the relative sliding of their side surfaces and appropriate friction force. The normal force value is changing with the parabolic function, which also leads to the changes of the friction force. The biggest value of the normal force and of the friction force is at the tooth root. Hollow between teeth and the tip of the pulley teeth are also in contact. Occasionally, the face surface of the belt and the flange are also in contact. The friction occurs in those tribomechanical systems, also. Values of these friction forces are lower compared with the friction force, which occurs at the teeth root.